Endovascular Treatment of Long Superficial Femoral Artery–Chronic Total Occlusions Using the Gogo Catheter With IVUS Via a Popliteal Puncture Method Is Effective, Safe, and Useful. (April 2020) - Nakamura, Shinichi; Rokutanda, Taku; Kurokawa, Hirofumi; Onoue, Yoshirou
Objectives: We aimed to investigate the usefulness of inserting a 6Fr sheath guided by duplex ultrasonography via a popliteal artery puncture. We also aimed to demonstrate endoluminal tracking using a retrograde approach using the Gogo catheter with intravascular ultrasound (IVUS). Background: The bidirectional approach is useful for increasing the success rate of the procedure for long superficial femoral artery–chronic total occlusions (SFA-CTOs). However, this procedure becomes somewhat complicated. Since the proximal blood vessel diameter is clearly larger than the distal end of the CTO and the body surface duplex guide can also be used in the proximal part, it is easier to introduce a retrograde guidewire (GW) into the proximal end. Methods: We performed endovascular treatment for long SFA-CTOs with a Gogo catheter + IVUS guide in 31 consecutive cases (male 20/female 11; mean age, 75.6 ± 7.6) from May 2017 to November 2018. We advanced the IVUS until the true lumen could be confirmed and advanced the Gogo catheter toward the IVUS for reinforcement. We attempted to approach the long CTO by repeating this procedure. We named this procedure the GIP method (GIP: Gogo catheter with IVUS via a popliteal puncture). Hemostasis of the popliteal artery was achieved using a commercially available compression hemostatic kit (Tometa-kun, XEMEX, Japan). Results: Successful revascularization was achieved in all cases (in 2 cases, a femoral artery puncture was added, and a bidirectional approach was used, and in 1 case, a CROSSER system was used). On average, the fluoroscopy time was 42.2 ± 30.4 minutes, radiation dose 93.7 ± 78.7 mGy, and amount of contrast medium used 15.0 ± 9.6 mL. The procedure time was defined as from the start of the popliteal artery puncture to the time the GW passed through the CTO lesion, including the posture transformation time from prone to the supine position. The procedure time was 42.1 ± 40.2 minutes. There were no major adverse events or other major complications, such as a distal embolism, rupture of the CTO lesion, arteriovenous fistula, or major hematoma requiring a transfusion or surgical treatment. Only 2 small hematomas occurred at the popliteal artery puncture site. The patients were treated conservatively and were discharged as usual. Conclusions: Endovascular treatment of long SFA-CTOs via the popliteal approach was effective and safe. Using the GIP method to address long SFA-CTOs is recommended.